2002
DOI: 10.1046/j.1365-2249.2002.01847.x
|View full text |Cite
|
Sign up to set email alerts
|

TCR usage and cytokine expression in peripheral blood and BAL T cells

Abstract: SUMMARY T cells are thought to play an important regulatory role in atopic asthma. We hypothesized that human blood and BAL T cell subsets bearing various TCR-Vβ genes might show selective differences in their cytokine profile. Peripheral blood (PB) and bronchoalveolar lavage (BAL) T cells from seven atopic asthmatic and six non-atopic non-asthmatic subjects were stimulated with PMA and ionomycin in the presence of monensin and analysed for TCR-Vβ expression and production of cytokines at the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Interestingly, ROBINSON et al [29] reported activation of CD4+ T cells in humans with allergic asthma and postulated that cytokines produced by activated Th2-type CD4+ T-cells may contribute to LAR. Th1 and Th2 responses, including cytokine-and chemokine-mediated responses, are well documented in allergic asthma [30][31][32]. Our observations indicate that activation state might be more critical than absolute numbers of T-cell subpopulations in establishing chronic disease.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, ROBINSON et al [29] reported activation of CD4+ T cells in humans with allergic asthma and postulated that cytokines produced by activated Th2-type CD4+ T-cells may contribute to LAR. Th1 and Th2 responses, including cytokine-and chemokine-mediated responses, are well documented in allergic asthma [30][31][32]. Our observations indicate that activation state might be more critical than absolute numbers of T-cell subpopulations in establishing chronic disease.…”
Section: Discussionmentioning
confidence: 68%
“…These analyses demonstrated that the immune reaction in sarcoidosis was strongly compartmentalized and that interstitium and alveolar region differ in the composition of the T cell subpopulation (13). However, bronchoalveolar T cells may only reflect a small part of the lung T cell pool (13)(14)(15)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“… 20 Similarly, another study demonstrated that the percentage of total CD3+ T cells in peripheral blood was similar in asthmatic patients and healthy control subjects. 21 …”
Section: Discussionmentioning
confidence: 99%